2017
DOI: 10.1111/jgs.14523
|View full text |Cite
|
Sign up to set email alerts
|

A Population‐Based Study Examining Injury in Older Adults with and without Dementia

Abstract: Older adults with dementia are at greater risk of a hospital admission for an injury. Multifactorial injury prevention programs would benefit older adults with and without dementia, especially those aged 85 and older, living alone, and with a history of previous falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
(56 reference statements)
1
27
0
Order By: Relevance
“…Those living alone are often responsible for their household [23, 24], and they might lack informal caregivers nearby [25]. Further, older adults living alone are often independent and eager to remain in their home as long as possible [26], a goal which can be threatened by a diagnosis of MCI or AD.…”
Section: Introductionmentioning
confidence: 99%
“…Those living alone are often responsible for their household [23, 24], and they might lack informal caregivers nearby [25]. Further, older adults living alone are often independent and eager to remain in their home as long as possible [26], a goal which can be threatened by a diagnosis of MCI or AD.…”
Section: Introductionmentioning
confidence: 99%
“…) and dementia (Axmon et al . ; Meuleners and Hobday ), as well as to be prescribed drugs known to increase the risk of falls, such as antidepressants, anxiolytics and hypnotics (Enderlin et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…During the entire lifespan, people with ID are consistently found to have lower balance and gait capacities (Enkelaar et al 2012), as well as poor perceptualmotor coordination (Carmeli et al 2008;Boot et al 2013). They are more likely to have medical conditions known to affect fall risk, such as epilepsy (Lukaszyk et al 2016;Cooper et al 2017), diabetes mellitus (Vinik et al 2017) and dementia Meuleners and Hobday 2017), as well as to 200 be prescribed drugs known to increase the risk of falls, such as antidepressants, anxiolytics and hypnotics (Enderlin et al 2015). Thus, potential ways of decreasing the prevalence of falls among older people with ID may be physical activity and physiotherapeutic interventions (Bartlo & Klein 2011;Van Hanegem et al 2014;Hale et al 2016) and regular drug reviews.…”
Section: Discussionmentioning
confidence: 99%
“…The final cluster of commentaries gives an overview of three different topics. Meuleners et al 13 analysed 29 671 hospital admissions and identified that older adults with dementia are at greater risk for admission to hospital with an injury 13. Next, Olsen et al found in their randomised trial that when a dog was added to activities of those with severe dementia in nursing homes, there was a significant decrease in the levels of depression and a positive impact on quality of life of the residents 14.…”
Section: Key Themesmentioning
confidence: 99%